Pendampingan Pengelolaan Keuangan Pada UMKM Kuliner My Kitchen Di Samarinda Dalam Mendukung Keberlanjutan Usaha - Yunita Fitria; Ferry Diyanti; Anisa Kusumawardani; Muhammad Abadan Syakura; Yoremia Lestari Ginting; Fibriyani Nur Khairin; Muhammad Haris Zidni Khatib Ramadhani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve financial management skills of the culinary MSME My Kitchen in Samarinda through assitance in simple finacial recording. The main problem faced by the partner is the absence of systematic financial records, making it difficult to determine busniss financial conditions accurately. The implementation method includes preparation, mentoring activities, and evaluation. The mentoring process was carried out  through financial literacy education, training on simple bookkeeping, and direct practice in recording daily transactions. The results show that the partner has improved unterstanding basuc finanvial management and is able to record income and expenses sytematically. In addition, the patmer can estimate business profits more accurately. This activity has a positive impact on improving financial literacy and supports the sustainability of the MSME business.